Pengaruh Pola Mengajar Guru Pendidikan Agama Islam terhadap Pemahaman Keislaman Siswa di SMP Negeri 32 Palembang - Fardinan Ramadhan; Azawar Hadi; Antoni Antoni (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study was conducted to identify the teaching patterns of Islamic Religious Education teachers, examine students' level of understanding, and analyze the influence of Islamic Religious Education teachers' teaching patterns on students' understanding at SMP Negeri 32 Palembang. The study aimed to provide a clear description of the effectiveness of teachers' instructional patterns in improving students' understanding and to serve as a basis for evaluation and improvement of the Islamic Religious Education learning process in schools. This research employed a quantitative approach using a survey method. The research instrument was a questionnaire based on a Likert scale consisting of 30 statements, with 15 items measuring the teaching patterns of Islamic Religious Education teachers and 15 items measuring students' understanding. The respondents were 57 students from SMP Negeri 32 Palembang. The collected data were analyzed using a correlation test to determine the relationship between the two research variables. The findings revealed a correlation coefficient of 0.042, indicating that there was no significant relationship between the teaching patterns of Islamic Religious Education teachers and students' understanding of Islamic teachings at SMP Negeri 32 Palembang. These findings suggest that students' understanding of Islam may be influenced by factors other than teachers' instructional patterns. Therefore, further research is recommended to identify other factors that may contribute to students' understanding of Islamic teachings.